Thoracic endovascular aortic repair for the ascending aorta: experience and pitfalls - Plichta, Ryan P. (J Vis Surg, 2018)
Thoracic endovascular aortic repair (TEVAR) of the ascending aorta is a developing alternative treatment strategy, which currently is specifically aimed at patients who are too high risk for open surgery. TEVAR has been applied to patients with a variety of pathologies of the ascending aorta including type A dissection, intramural hematoma (IMH), penetrating ulcers, aneurysm and pseudoaneurysm. Here we discuss the current evidence regarding the use of TEVAR for the ascending aorta as well as the latest techniques and pitfalls of the procedure. The challenges of this modality are considerable, and the techniques that have been applied draw from the many facets of endovascular experience. There is limited literature regarding the use of stent grafts in the ascending aorta, and the pool of patients currently considered appropriate candidates for the procedure is small. This is an evolving intervention that warrants further study and the development of devices specifically engineered to meet the anatomical and physiologic challenges of the ascending aorta.